Thin films based on Er3+ doped germanate-tellurite nanoglasses for Plasmonics - Ricaldi, José Yitzhak Aarón Chacaliaza (2023)
Er3+-doped germanate-tellurite glasses were synthesized using the conventional meltquenching technique. The glass samples were melted at 900 ºC and subsequently subjected to heat treatment at 290 ºC. Optical characterization of the glasses included refractive index measurements, photoluminescence, radiative lifetime decay, and UV-VIS-NIR absorption spectroscopy were performed. Additionally, the influence of Er3+ doping on the glass structure was investigated using FTIR, Raman spectroscopy, and X-ray diffraction. The second part of this dissertation focused on fabricating nanostructured glasses (nanoglasses) and plasmonic metasurfaces on gold thin film. The nanoglasses were mixed in a solution of polymethyl methacrylate and deposited on the metasurfaces using spincoating. The roughness and thickness of the thin films were characterized using atomic force microscopy and contact profilometry. The luminescence properties of the thin film were examined using fluorescence confocal microscopy. The confocal optical microscopy and confocal lifetime fluorescence techniques were used to investigate the coupling mechanisms between surface plasmons polaritons located on the metasurface and the rare-earth ions. It was observed that when Er3+ ions are located close to the surface, there is a strong coupling mechanism between them due to the reduction in the radiative lifetime of the Er3+ emitter. This coupling is more evident in smaller nanoparticles, that is, closer to the interface. The results show the possibility of developing photonic devices using this platform.